Expectations of emerging adults about conjugality and parenthood - Ferreira, Margarida Amaro (2022)
In modern societies the life course up to the point of marriage and having children is not as linear as it was in the past. For this reason, this study aimed to analyse the factors that may influence the expectations of emerging adults on conjugality and parenthood, such as academic ambition, family typology, and religion. This is an exploratory research, with qualitative design, in which 18 emerging adults living in Portugal participated in individual semi-structured interviews. Thematic analysis suggests that emerging adults perceive personal over external factors as having greater impact on what they expect of conjugality and parenthood. The current study also highlights a general preference for marriage as opposed to cohabitation, and points to a tendency, on the part of religious emerging adults, to prefer to marry through the church. The findings of this study may contribute to better interventions in different contexts with emerging adults, and may have expanded the knowledge about what their main concerns are, regarding the constitution of a family.